Climate change impact, adaptation and mitigation in agriculture: methodology for assessment and applications - Pathak, Himanshu; Aggarwal, Pramod K.; Singh, S.D. (Indian Agricultural Research Institute, 2012)
Climatic changes and increasing climatic variability are likely to aggravate the problem of future food security by exerting pressure on agriculture. However, there are lot of uncertainties about the assessment of impact, adaptation and mitigation of climate change in agriculture. It is largely because the methodology followed for such assessments is not standardized and sometimes it is inaccurate and imprecise. Researchers follow different methodologies and arrive at contrasting results making it difficult to reach a logical conclusion and develop policy actions. There is a need to develop and apply a standard methodology across the board for various studies related to climate change and agriculture.